The burden and risks of pediatric pneumonia in Nigeria: A desk‐based review of existing literature and data. Issue 1 (27th January 2020) - Iuliano, Agnese; Aranda, Zeus; Colbourn, Tim; Agwai, Imaria C.; Bahiru, Solomon; Bakare, Ayobami A.; Burgess, Rochelle A.; Cassar, Christine; Shittu, Funmilayo; Graham, Hamish; Isah, Adamu; McCollum, Eric D.; et al.
Abstract: Background: Pneumonia is a leading killer of children under‐5 years, with a high burden in Nigeria. We aimed to quantify the regional burden and risks of pediatric pneumonia in Nigeria, and specifically the states of Lagos and Jigawa. Methods: We conducted a scoping literature search for studies of pneumonia morbidity and mortality in under‐5 children in Nigeria from 10th December 2018 to 26th April 2019, searching: Cochrane, PubMed, and Web of Science. We included grey literature from stakeholders' websites and information shared by organizations working in Nigeria. We conducted multivariable logistic regression using the 2016 to 2017 Multiple Cluster Indicators Survey data set to explore factors associated with pneumonia. Descriptive analyses of datasets from 2010 to 2019 was done to estimate trends in mortality, morbidity, and vaccination coverage. Results: We identified 25 relevant papers (10 from Jigawa, 8 from Lagos, and 14 national data). None included data on pneumonia or acute respiratory tract infection burden in the health system, inpatient case‐fatality rates, severity, or age‐specific pneumonia mortality rates at state level. Secondary data analysis found that no household or caregiver socioeconomic indicators were consistently associated with self‐reported symptoms of cough and/or difficulty breathing, and seasonality was inconsistently associated, dependant on region. Conclusion: There is a clear evidence gap around the burden of pediatric pneumonia in Nigeria, and challenges with the interpretation of existing household survey data. Improved survey approaches are needed to understand the risks of pediatric pneumonia in Nigeria, alongside the need for investment in reliable routine data systems to provide data on the clinical pneumonia burden in Nigeria.